(untitled) (Ibrahim Cardiac Medical Journal, 2019)
Transradial access has now a days become a standard of care for percutaneous coronary angiography & intervention. This approach has demonstrated significant reduction in bleeding rate, length of hospital stay and improvement in clinical outcomes when compared to the traditional TF approach. However this novel approach may lead to severe catheter kinking & twisting and further manipulation may require unraveling the catheter and avoiding complication. The fracture of a guide catheter is an uncommon complication during percutaneous coronary intervention (PCI). It sometimes occurs during engagement of the right coronary ostium, when there is excessive twisting of the guide catheter. An interesting case of complete fracture of a 6 Fr Ikari guide catheter in the brachial artery during transradial coronary intervention is presented. Ibrahim Card Med J 2018; 8 (1&2): 66-70